Genetic Diversity of Multidrug-Resistant Pseudomonas aeruginosa Isolates Carrying blaVIM–2 and blaKPC–2 Genes That Spread on Different Genetic Environment in Colombia - Rada, Ana M.; De La Cadena, Elsa; Agudelo, Carlos A.; Pallares, Christian; Restrepo, Eliana; Correa, Adriana; Villegas, María V.; Capataz, Cesar (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen with an increase in the frequency of infections caused by multidrug resistant (MDR) and extensively drug resistant (XDR) strains, limiting the available therapeutic options. The most troublesome resistance is the acquisition and production of carbapenemases such as Verona Integron-encoded Metallo--lactamases (VIM) the most frequent and widespread, and the Klebsiella pneumoniae carbapenemases (KPC) which has continuously spread in the last decade. Its dissemination is linked to their location on mobile genetic elements (MGEs). In Colombia, VIM and KPC have been increasing in its frequency showing major successful dissemination. In this article, we molecularly characterized and analyzed the genetic context of blaVIM and blaKPC in carbapenem-resistant P. aeruginosa (CRPA) isolates from infected and colonized patients in two tertiary-care hospitals, one in Medellín and the other in a municipality close to Medellín, both areas with high carbapenemase endemicity in Colombia (2013-2015). Using whole-genome sequencing (WGS) we identified a remarkably variety of genetic backgrounds in these MDR P. aeruginosa isolates carrying the blaKPC-2 and blaVIM-2. There were a diversity of class 1 integron and variations in the gene cassettes associated to blaVIM-2, as well as a possible event of spread of blaKPC-2 mediated by a plasmid that contained part of the Tn4401b in one infection case. The dissemination of blaVIM-2 and blaKPC-2 in P. aeruginosa in this area in Colombia has been strongly influence by successful international clones, carrying these genes and additional determinants of resistance on mobile genetic elements, accompanied by gene rearrangement under an antimicrobial selection pressure. These findings emphasize the need to implement control strategies based on rational antibiotic use.